Des principes d’une cinémathèque dédiée aux « jeunes publics » : La cinémathèque Robert-Lynen - Emmanuelle Devos (Conserveries Mémorielles)
Giving access to educational films was determining in creating the City of Paris filmlibrary in 1925. But since then the institution stakes evolved and now exceed this original mission.Thanks to evoquing the founding principles of the filmlibrary , this paper highlights how educating young audiences is an important and sensitive issue in a context of massive distribution of images.Today many institutions special programms dedicated to young people, as the status of the image in society changes and demands of this specific audience grow. The history of the City of Paris filmlibrary helps to perceive how this major issue has evolved until nowadays.